From Beliefs To Budgeting: How Locus Of Control And Financial Literacy Influence Financial Planning? - Aslam, Annisa Paramaswary; Putra, Muh. Al Fatah Arief; Patigana, A Gita Namira; Kesuma, Sulfadli Adi Jaya; Saputra, Aria (Universitas Muhammadiyah Palembang, 2024)
This study aims to explore the impact of locus of control, love of money, and financial literacy on financial planning, and to understand how financial literacy moderates the relationship between these factors and financial planning. The findings indicate that both locus of control and love of money have a significant positive impact on financial planning. Conversely, financial literacy has a significant negative effect on financial planning and does not significantly moderate the relationship between love of money and financial planning. This suggests that, although financial literacy is crucial, the overconfidence often associated with high levels of financial literacy can lead to riskier financial decision-making. The study highlights the need to consider psychological factors such as locus of control and love of money in financial planning, as well as the importance of managing overconfidence in financial literacy to avoid suboptimal financial decisions. Additionally, this study is important for individuals of productive age who are investing their money